منهج المحدثين النقدي من وجهة نظر عبدالله العروي: دراسة تحليلية نقدية - دعوري، محمد بن أحمد بن إبراهيم (جامعة الملك عبدالعزيز, 2023)
هذا البحث يتناول آراء العروي عن منهج المحدثين كأداة ناقدة، وتقع أهمية البحث بأنه يتناول قضية منهجية متعلقة بطريقة النقد التي مارسها علماء الحديث، وأن هذه الطريقة يمكن استثمارها في ميادين أخرى (كميدان علم التاريخ)، فتغدوا المدرسة الحديثية في النقد مدرسة منتجة وليست جامدة، مدرسة شمولية بعيدة عن التحديدات الزمانية والمكانية، ويهدف البحث إلى هدفين: الأول: الكشف عن تصور عبدالله العروي عن المنهج النقدي لدى المحدثين الثاني: دراسة آراء العروي عن منهج المحدثين والرد عليها، وقسمت البحث إلى مقدمة، وستة مباحث، وجعلت له خاتمة ذكرت فيها النتائج التي توصلت إليها في البحث، وكأن أهمها: أن المنهج الغربي في نظرته للتاريخ منهجا مشتتا، ولا يمكن الاقتصار على لآلياته بشكل منفرد، وأنه يمكن توظيف أداة المحدثين الناقدة المستعملة في نقد الأحاديث النبوية لنقد التاريخ، وذلك بالمحاكمة إليها كأداة ناقدة، لا كأداة متخصصة في ميدان الحديث النبوي، وذلك من خلال استثمار المنهجيات الحديثية في إنتاج أدوات النقد. This research tackles the critical modernist approach for Dr. Abdullah Laroui in his cultural project, through his book (the Concept of History) as a basic entrance in stating the topics of this research. Through this statement, I would like to indicate the committed disorder by the doctor when tackling the modernist approach and the reductionist sight, upon which he has understood this critical approach. He protested that the modernist approach can be a productive approach in a field other than the basic field, in which it was originated. This indicates that the exploitation of the used criticism aspects by the prophet traditions scientists is a thoughtful and coherent approach that can be productive in multiple fields, including the historical field. Noting that the thing that leads many orientalists, and the modernists after them, in their misconceptions towards the modern critical approach trend is their dependence on literature which were originated in the prophet traditions science without reviewing the original books which have set the prophet tradition science, so that the practices shall be consonant with the term when tackled and treated in the modern field. This leads to a disorder in the point of view for the modernist critical approach. This approach can only be understood through the used critical practices by imams. They are the practices which explain and manifest the term which has been called in the prophet traditions science. These terms cannot be regulated unless by the critical practices for the imams of this concern.
Keywords: النقد الحديثي -- العروي، عبدالله -- المناهج النقدية -- علماء الحديث